Reconstruction of arboreal vegetation dynamics of the area of Museum-Reserve Kulikovo Pole in the middle and late Holocene - Novenko, Elena Yu (Nature Conservation Research: Заповедная наука, 2017)
The paper presents reconstructions of vegetation and forest coverage dynamics in the area of the State Military-Historical and Natural Museum-Reserve «Kulikovo Pole» (Upper Don River basin) in the middle and late Holocene, based on modern and fossil pollen assemblages and remote sensing data (MODIS) using the «the Best Modern Analogue» technique for paleoecological studies. The data obtained showed that in the study area steppe vegetation was widespread in the period 7000–4500 cal. (calendar) years BP, forest coverage was 10–20%. Cooling and moistening of the climate around 4500 cal. years BP encouraged a shift of the forest-steppe boundary to the South; forest-steppe vegetation with the participation of pine and broad-leaved forests of Quercus, Tilia, Ulmus and Alnus occupied the Upper Don River basin. Meadow steppe plant communities persisted mostly on dry slopes and well-drained watersheds. The forest coverage increased to 30–40%, and around 2700 cal. years BP reached 45%. Significant changes in vegetation and reduction of the area covered by forest (to 15%) occurred at 2400 cal. years BP and were caused mainly by the anthropogenic factor. An extensive agriculture during the periods of human occupation resulted in a decrease in forest coverage, when the territory was abandoned forests recovered their areas.